2012
DOI: 10.3109/09540261.2012.707118
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia in women and children: A selective review of literature from developing countries

Abstract: Women and children with psychotic disorders in developing countries may be vulnerable and have considerable social disadvantages. Gender disadvantage has implications for all health outcomes including mental illnesses. In the more relevant gender-related context we discuss several important issues which affect women with schizophrenia, namely stigma, caregiver burden, functional outcome, marriage, victimization and help-seeking. The findings indicate that there are variations in clinical and functional outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 108 publications
0
10
0
Order By: Relevance
“…Studies have reported that women and children with psychotic disorders in developing countries may be vulnerable and have considerable social disadvantages such as having difficulty in getting married, being thrown out of the house by the in-laws due to mental illness and the fear of being a burden to their parents. 16,17 The findings indicate that stigma is pervasive irrespective of the educational status or rank.…”
Section: Resultsmentioning
confidence: 92%
“…Studies have reported that women and children with psychotic disorders in developing countries may be vulnerable and have considerable social disadvantages such as having difficulty in getting married, being thrown out of the house by the in-laws due to mental illness and the fear of being a burden to their parents. 16,17 The findings indicate that stigma is pervasive irrespective of the educational status or rank.…”
Section: Resultsmentioning
confidence: 92%
“…In most low- and middle-income countries (LMICs), women with SMI experience multiple adversities due to untreated symptoms, functional impairment, limited access to treatment options, stigma, social exclusion and, more broadly, due to the sociocultural context that may disadvantage women in general [3, 4]. Women with SMI are at elevated risk of gender-based violence.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study from Nigeria, women with schizophrenia were at increased risk of intimate partner violence [5]. These gender disadvantages may translate into worse general health, economic, and social outcomes of SMI than men [3]. SMI is inextricably linked with poverty in most LMICs due to out of pocket healthcare financing and the long-term nature of the illness [6, 7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of studies from mostly high-income countries suggests that men with schizophrenia have almost equal recovery rates to women, with about one in seven people recovering over time (Jääskeläinen et al 2012). A literature review from low- to middle-income countries, however, suggests that there are sex differences in clinical and functional outcomes with psychotic women having poorer prognoses than their male counterparts, because of greater stigma, coercion and victimization, contributing to less help-seeking (Chandra et al 2012). If this is the case, then comparison outcomes from a mostly male sample would overestimate recovery, making our estimates of MHD outcomes conservative.…”
Section: Discussionmentioning
confidence: 99%